1998
DOI: 10.1523/jneurosci.18-22-09500.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Influence of Burst and Tonic Firing Mode on Synaptic Interactions in the Thalamus

Abstract: Thalamocortical and perigeniculate (PGN) neurons can generate action potentials either as Ca2+ spike-mediated high-frequency bursts or as tonic trains. Using dual intracellular recordings in vitro in monosynaptically connected pairs of PGN and dorsal lateral geniculate nucleus (LGNd) neurons, we found that the functional effect of synaptic transmission between these cell types was strongly influenced by the membrane potential and hence the firing mode of both the pre- and postsynaptic neurons. Activation of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 84 publications
(87 reference statements)
7
102
1
2
Order By: Relevance
“…1F). There was no voltage envelope below the bursts as in thalamic relay neurons (19). At even higher frequencies these bursts fused, leading to continuous spiking and a drop in CV ISI below 0.5 in five of eight cells tested above a cell-specific frequency.…”
Section: Resultsmentioning
confidence: 86%
“…1F). There was no voltage envelope below the bursts as in thalamic relay neurons (19). At even higher frequencies these bursts fused, leading to continuous spiking and a drop in CV ISI below 0.5 in five of eight cells tested above a cell-specific frequency.…”
Section: Resultsmentioning
confidence: 86%
“…Studies on thalamic relay neurons have shown that relatively small changes in membrane potential can have dramatic consequences on neuronal firing (McCormick and Pape, 1990;Kim and McCormick, 1998). The apparent decrement in the effect of NT-3 on APmax from P10 to P14 was surprising given that P8 base neurons responded robustly.…”
Section: Resultsmentioning
confidence: 99%
“…5B). This happened because the slow EPSP decay time constant in RS and SOM cells (Table 2), relative to the short intraburst ISIs, enabled temporal summation (Kim and McCormick, 1998;Usrey et al, 2000) and also (in SOM cells) because of the absence, on average, of short-term depression (Figs. 1R, 3L;Beierlein et al, 2003;Minneci et al, 2007;Tan et al, 2008;Takesian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The combined result is that the first spike in the burst will activate a relatively undepressed synapse and elicit a considerably larger excitatory response compared with the average single spike (Swadlow and Gusev, 2001). Bursts could also enhance the postsynaptic response through temporal summation, when successively arriving EPSPs accumulate faster than they can dissipate (Kim and McCormick, 1998;Usrey et al, 2000). Conversely, high-frequency firing causes strong short-term depression of many thalamocortical synapses (Galarreta and Hestrin, 1998;González-Burgos et al, 2004;Gabernet et al, 2005;Kloc and Maffei, 2014), counteracting temporal summation.…”
Section: Introductionmentioning
confidence: 99%